Corrosion Rate and Residual Stress on GMAW Weld Joint of SUS 304 Steel with Static Thermal Tensioning Treatment - R.N. Akhsanu Takwim; Anggit Murdani; Bayu Pranoto (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
One of the biggest problems in the metal welding process, especially for stainless steel, is the occurrence of large distortions. To reduce distortion during the welding process, it is recommended to provide secondary thermal like Static Thermal Tensioning. However, the provision of secondary thermal is allegedly able to decrease residual stress but reduce the corrosion resistance of stainless steel . In this study, variations in temperature of static thermal tensioning were applied during the GMAW process of SUS 304 plate. Furthermore, the results of the welding were made test specimens to determine the residual stress and corrosion rate of each temperature variation. The measurement of the residual stress using slitting method and measurements of the corrosion rate was carried out with the Autolab PGSTAT 204 potentiostat. The measurement results showed that residual stress of the welding results decrease along with the increase in the temperature of the Static Thermal Tensioning treatment where the treatment temperature of 200 ºC have highest residual stress at 113.79 MPa, followed by the treatment temperature of 250 ºC with 105.67 MPa value, and the lowest residual stress at temperature of 300 ºC with 77.82 MPa value. But, the corrosion rate value at the opposite way where the treatment temperature of 200 ºC produces the lowest corrosion rate, which is 0.70 mm/year, followed by the treatment temperature of 250 ºC of 0.99 mm/year and at a treatment temperature of 300 ºC with a corrosion rate of 1.27mm/year.